2016
DOI: 10.18632/oncotarget.7720
|View full text |Cite
|
Sign up to set email alerts
|

CD40-activated B cells induce anti-tumor immunityin vivo

Abstract: The introduction of checkpoint inhibitors represents a major advance in cancer immunotherapy. Some studies on checkpoint inhibition demonstrate that combinatorial immunotherapies with secondary drivers of anti-tumor immunity provide beneficial effects for patients that do not show a strong endogenous immune response. CD40-activated B cells (CD40B cells) are potent antigen presenting cells by activating and expanding naïve and memory CD4+ and CD8+ and homing to the secondary lymphoid organs. In contrast to dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…Body weight and survival remained unchained under all tested conditions. No abnormal lymphocytic infiltration, structural tissue injury, or indications of inflammation could be detected in histological analyses of heart, lung, liver, spleen, and kidney [68]. These results are in line with a study where administration of RNA-loaded CD40B cells was well tolerated by dogs with non-Hodgkin’s lymphoma and no long-term complications were observed in the follow-up [69].…”
Section: B Cells For Immunotherapysupporting
confidence: 81%
See 1 more Smart Citation
“…Body weight and survival remained unchained under all tested conditions. No abnormal lymphocytic infiltration, structural tissue injury, or indications of inflammation could be detected in histological analyses of heart, lung, liver, spleen, and kidney [68]. These results are in line with a study where administration of RNA-loaded CD40B cells was well tolerated by dogs with non-Hodgkin’s lymphoma and no long-term complications were observed in the follow-up [69].…”
Section: B Cells For Immunotherapysupporting
confidence: 81%
“…However, these studies used soluble anti-CD40 antibodies for the activation of B cells, which was demonstrated to result in weaker CD40 stimulation than activation by CD40L-expressing feeder cells [21, 31]. When using CD40L-expressing feeder cells for activation, vaccination with tumor antigen-pulsed CD40B cells before B16 melanomas or E.G7 lymphomas were injected [68] resulted in significantly delayed growth in both tumor models. The rate of tumor control by CD40B cell vaccination was comparable to that induced by DCs.…”
Section: B Cells For Immunotherapymentioning
confidence: 99%
“…At the same time, the antigen‐specific B cells can also differentiate into plasma cells to reinforce antitumor effects and to diminish established tumors. Indeed, CD40‐activated B cells have been widely studied, which activating and promoting the proliferation of T cell to induce antitumor immunity by acting as APCs …”
Section: Dual Aspects Of the Biological Function Of B Cellsmentioning
confidence: 99%
“…Such activated B cells increased expression of costimulatory and MHC molecules [16,[18][19][20] rendering them attractive for vaccination. It was shown by several groups that mouse and human CD40 activated B (CD40-B) cells could present a variety of MHC class I and II epitopes to T cells [16][17][18][19][20][21][22][23][24]. Furthermore, we, and others, have shown that CD40-B cells can prime naive CD8 + T-cell response in vivo [16][17][18][19]22].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown by several groups that mouse and human CD40 activated B (CD40-B) cells could present a variety of MHC class I and II epitopes to T cells [16][17][18][19][20][21][22][23][24]. Furthermore, we, and others, have shown that CD40-B cells can prime naive CD8 + T-cell response in vivo [16][17][18][19]22]. Preclinical vaccination studies in mice and dogs have shown their potential for cancer immunotherapy [16,18,22,25].…”
Section: Introductionmentioning
confidence: 99%